A snapshot of High-Performance Organization (HPO) / Azfahanee Zakaria, Syed Mohammed Alhady Syed Ahmad Alhady and Sarah Sabir Ahmad - Zakaria, Azfahanee; Syed Ahmad Alhady, Syed Mohammed Alhady; Sabir Ahmad, Sarah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
In creating and sustaining a growth of organization, many issues are discussed at all levels, either the lower level in the organization, middle or even at the highest level of management in the organization. The success of the organization is definitely the interest of all employees as it has direct impact towards the employees’ career, rewards and satisfaction level. The interest and concern have led to the discussion on the High Performance Organization.